(untitled) (Journal of Health, Population and Nutrition, 2009)
Acute gastrointestinal illness is an important public-health issue worldwide. Burden-of-illness studies have not previously been conducted in Cuba. The objective of the study was to determine the magnitude, distribution, and burden of self-reported acute gastrointestinal illness in Cuba. A retrospective, cross-sectional survey was conducted in three sentinel sites during June-July 2005 (rainy season) and during November 2005-January 2006 (dry season). Households were randomly selected from a list maintained by the medical offices in each site. One individual per household was selected to complete a questionnaire in a face-to-face interview. The case definition was three or more bouts of loose stools in a 24-hour period within the last 30 days. In total, 97.3% of 6,576 interviews were completed. The overall prevalence of acute gastrointestinal illness was 10.6%. The risk of acute gastrointestinal illness was higher during the rainy season (odds ratio [OR]=3.85, 95% confidence interval [CI] 3.18-4.66) in children (OR=3.12, 95% CI 2.24-4.36) and teens (OR=2.27, 95% CI 1.51-3.41) compared to people aged 25-54 years, in males (OR=1.24, 95% CI 1.04-1.47), and in the municipality of Santiago de Cuba (OR=1.33, 95% CI 1.11-1.61). Of 680 cases, 17.1-38.1% visited a physician, depending on sentinel site. Of the cases who visited a physician, 33.3-53.9% were requested to submit a stool sample, and of those, 72.7-100.0% complied. Of the cases who sought medical care, 16.7- 61.5% and 0-31.6% were treated with antidiarrhoeals and antibiotics respectively. Acute gastrointestinal illness represented a substantial burden of health compared to developed countries. Targeting the identified risk factors when allocating resources for education, food safety, and infrastructure might lower the morbidity associated with acute gastrointestinal illness. Key words: Cross-sectional studies; Developing countries; Diarrhoea; Epidemiology; Public health; Retrospective studies; Risk factors; Seasonal variation; Sentinel sites; Cuba doi: 10.3329/jhpn.v27i3.3377 J Health Popul Nutr 2009 Jun;27(3):345-357